The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/340626
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Fermented Soybean Dried Extracts against TPA-Induced Oxidative Stress in Hairless Mice Skin

Abstract: This study evaluated the chemical properties (polyphenol and genistein contents) of soybean extracts obtained by biotransformation and dried by spray dryer at different conditions and their in vivo ability to inhibit 12-O-tetradecanoylphorbol-13-acetate- (TPA-) induced biochemical alterations in the skin of hairless mice. By comparing the obtained data with that of the well-known active soybean extract Isoflavin beta, we evaluated the influence of the fermentation and drying process in the extracts efficacy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Recent data indicated that isoflavones, via binding to ERα, promote cell proliferation, but via binding to ERβ, promote apoptosis [4]. Furthermore, they can act as antioxidants by scavenging free radicals and/or chelating metal ions [5,6]. Isoflavones exhibit anti-inflammatory [7], anti-allergic as well as anti-cancer properties [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data indicated that isoflavones, via binding to ERα, promote cell proliferation, but via binding to ERβ, promote apoptosis [4]. Furthermore, they can act as antioxidants by scavenging free radicals and/or chelating metal ions [5,6]. Isoflavones exhibit anti-inflammatory [7], anti-allergic as well as anti-cancer properties [8].…”
Section: Introductionmentioning
confidence: 99%
“…Isoflavones exhibit anti-inflammatory [7], anti-allergic as well as anti-cancer properties [8]. Daidzein and genistein are the two main and most well characterized isoflavones present in soybean, able to inhibit transcription factors NF-κβ, Aκt and AP-1 signalling pathway [6,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that fermentation enhances polyphenol bioactivity [8688], suggesting that fermentation results in the conversion of polyphenols with large molecular weights to compounds of low molecular weight, which have more biological activity. Under aerobic conditions where fermentation is influenced by oxygen, oxidized structures are generated, giving rise to lower-molecular-weight compounds that are converted into mono-aromatic acids and CO 2 [89]. …”
Section: Discussionmentioning
confidence: 99%
“…[328][329][330][331][332][333] Even though genistein has skin protecting activity and enhances beauty, its sustained effect is still limited due to lower stability in cosmeceutical products. In order to enhance stability and prolong activity, nanosized delivery technologies have greater impact in cosmeceutical sectors.…”
Section: Nanogenisteinmentioning
confidence: 99%